Structure and Surface Relaxation of CeO2 Nanoparticles Unveiled by Combining Real and Reciprocal Space Total Scattering Analysis - Marco Scavini; Federica Bertolotti; Jonadri Mlloja; Filippo Umbri; Anna Bosc; Serena Cappelli; Stefano Checchia; Cesare Oliva; Patrizia Fumagalli; Davide Ceresoli; Mariangela Longhi; Antonietta Guagliardi; et al. (Nanomaterials, 2022)
We present a combined real and reciprocal space structural and microstructural characterization of CeO2 nanoparticles (NPs) exhibiting different crystallite sizes; ~3 nm CeO2 NPs were produced by an inverse micellae wet synthetic path and then annealed at different temperatures. X-ray total scattering data were analyzed by combining real-space-based Pair Distribution Function analysis and the reciprocal-space-based Debye Scattering Equation method with atomistic models. Subtle atomic-scale relaxations occur at the nanocrystal surface. The structural analysis was corroborated by ab initio DFT and force field calculations; micro-Raman and electron spin resonance added important insights to the NPs’ defective structure. The combination of the above techniques suggests a core-shell like structure of ultrasmall NPs. These exhibit an expanded outer shell having a defective fluorite structure, while the inner shell is similar to the bulk structure. The presence of partially reduced <semantics><msubsup>O2−δ</msubsup></semantics> species testifies to the high surface activity of the NPs. On increasing the annealing temperature, the particle dimensions increase, limiting disorder as a consequence of the progressive surface-to-volume ratio reduction.